Analisis Non Performing Financing, Dana Pihak Ketiga, Capital Adequacy Ratio, Dan Financing To Deposit Terhadap Total Pembiayaan - Vivin Andriani; Mukhaer Pakkanna (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
This research aims to examine the effect of Non-Performing Financing (NPF), Third Party Fund (DPK), CAR and FDR both simultaneously or partially on Total Financing with Islamic General Bank. In this research, the researcher applied quantitative method and employed secondary type of data sources. The sample used in this research is financial statement Islamic General Bank during the period of 2013-2017. The data analysis method used in this research is variable descriptive statistics, classic assumption test, multiple linear regression with significance level 5% and hypothetical test. The outcome of the research is processed using SPSS program version 22